الانتباه البصري لدى عينة من الأطفال المعسرين قرائيا ة في الطور السنة الثالث والرابعة ابتدائي - بركة فاطمة; بوخلط وسيلة; بن يحي مداني (My University, 2021)
The current study aims to study the visual attention of the dyslexic of third and fourth year students of primary school by using the holiday text test for Ghalab Saliha and the visual attention test K-ABC. This study was carried out at the Muhaigira Abd al-Qader Foundation in Laghouat. The study sample consisted of (5) students (two girls and three males), based on the descriptive method for its .relevance to our study :Our study started from the following questions ?Do dyslexics suffer from visual attention ?Does visual attention affect dyslexics Based on previous studies and theoretical literature, we formulated the following :hypotheses Dyslexics suffer from visual attention function - After applying the mentioned test and interpreting the results, the researchers .concluded that the hypotheses were not verified